PEDOT:PSS: A Conductive and Flexible Polymer for Sensor Integration in Organ-on-Chip Platforms. (2016) - Quirós-Solano, W.F.; Gaio, N.; Silvestri, C.; Pandraud, G.; Sarro, P.M.
Abstract: Sensing and stimulating microstructures are necessary to develop more specialized and highly accurate Organ-on-Chip (OOC) platforms. In this paper, we present the integration of a conductive polymer, poly (3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), on a stretchable membrane, core element of an Heart-on-Chip. The electrical conductivity along with its biocompatibility, high transparency (≈88%) and mechanical elasticity (≈1.2 GPa) make this material a candidate to develop novel microstructures for electrical monitoring and stimulation of cells in flexible-substrate based OOCs. Microstructures with different shapes and geometries of PEDOT:PSS embedded in a 9 μm-thick Polydimethylsiloxane (PDMS) membrane are developed following a wafer-level fabrication approach. PEDOT:PSS layers between 120 nm and 300 nm are obtained by varying the deposition conditions. The layers are successfully patterned and microstructures with lateral dimensions down to 2 μm. The obtained results indicate that this polymer is a suitable material for microfabrication of sensing and stimulating elements in OOC platforms.